Oxygen consumption rate of sinking diatom aggregates incubated in rotating pressure and control tanks - Peter Stief (PANGAEA, 2023)
The effect of increasing hydrostatic pressure on the microbial degradation, the organic matter composition, and the microbiome of extquotesinglemarine snow extquotesingle particles was studied in laboratory incubation experiments. Model aggregates were produced from the diatom Skeletonema marinoi and the natural microbial community of surface seawater collected in the Kattegat. The aggregates were incubated individually in rotating pressure and control tanks to keep them suspended during 20-day incubations in the dark and at 3°C. In the pressure tanks, hydrostatic pressure was increased at increments of 5 MPa per day to finally reach 100 MPa. This pressure scheme simulates the descent of diatom aggregates from the surface ocean down into a 10-km deep hadal trench. In the control tanks, pressure was always left at atmospheric level. Volumetric oxygen consumption rates of sinking diatom aggregates were calculated from the temporal change in oxygen concentration in the water surrounding the aggregates and the individual aggregate volume and served as a proxy for aerobic microbial aggregate degradation.
In: Stief, Peter; Schauberger, Clemens; Becker, Kevin W; Elvert, Marcus; Balmonte, John Paul; Franco-Cisterna, Belén; Middelboe, Mathias; Glud, Ronnie N (2023): Effects of increasing hydrostatic pressure on sinking diatom aggregates [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.960357